‘Missing link’ species Capsella orientalis and Capsella thracica elucidate evolution of model plant genus Capsella (Brassicaceae) - Hurka, Herbert; German, Dmitry; Franzke, Andreas (Molecular ecology, 2012)
To elucidate the evolutionary history of the genus Capsella, we included the hitherto poorly known species C. orientalis and C. thracica into our studies together with C. grandiflora, C. rubella and C. bursa-pastoris. We sequenced the ITS and four loci of noncoding cpDNA regions (trnL - F, rps16, trnH -psbA and trnQ -rps16). Sequence data were evaluated with parsimony and Bayesian analyses. Divergence time estimates were carried out with the software package BEAST. We also performed isozyme, cytological, morphological and biogeographic studies. Capsella orientalis (self-compatible, SC; 2n = 16) forms a clade (eastern lineage) with C. bursa-pastoris (SC; 2n = 32), which is a sister clade (western lineage) to C. grandiflora (self-incompatible, SI; 2n = 16) and C. rubella (SC; 2n = 16). Capsella bursa-pastoris is an autopolyploid species of multiple origin, whereas the Bulgarian endemic C. thracica (SC; 2n = 32) is allopolyploid and emerged from interspecific hybridization between C. bursa-pastoris and C. grandiflora. The common ancestor of the two lineages was diploid and SI, and its distribution ranged from eastern Europe to central Asia, predominantly confined to steppe-like habitats. Biogeographic dynamics during the Pleistocene caused geographic and genetic subdivisions within the common ancestor giving rise to the two extant lineages.
Gesehen am 10.05.2017